Krisis Pengungsi di Sudan dan Dampaknya terhadap Stabilitas Keamanan Wilayah Perbatasan Chad - Andi Syakirah Nariswari; Imam Fadhil Nugraha (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This paper discusses the impact of the Sudanese refugee crisis on security stability in the Chad border region. The conflict between the Sudanese Armed Forces and Rapid Support Forces since April 2023 has triggered a massive wave of refugees, making Chad one of the main recipient countries. Using a regional security complex theory approach, this paper shows that the flow of refugees not only creates social and economic pressures, but also magnifies security risks such as infiltration of armed groups, tensions between communities, and weak control in the border region. Through document analysis, the paper highlights how Chad's capacity constraints exacerbate the situation, as well as the need for a long-term response involving cross-actor coordination and sustained international support.